2016
DOI: 10.1021/acs.nanolett.6b01044
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation, Growth, and Bundling of GaN Nanowires in Molecular Beam Epitaxy: Disentangling the Origin of Nanowire Coalescence

Abstract: We investigate the nucleation, growth, and coalescence of spontaneously formed GaN nanowires in molecular beam epitaxy combining the statistical analysis of scanning electron micrographs with Monte Carlo growth models. We find that (i) the nanowire density is limited by the shadowing of the substrate from the impinging fluxes by already existing nanowires, (ii) shortly after the nucleation stage, nanowire radial growth becomes negligible, and (iii) coalescence is caused by bundling of nanowires. The latter phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(95 citation statements)
references
References 66 publications
8
87
0
Order By: Relevance
“…However, the fraction of the surface area covered by the nanowires remains unchanged, which rules out radial growth of nanowires as the origin of coalescence. Instead, we have found that the nanowires bundle together after reaching a certain critical height to reduce the surface energy of their side facets at the expense of the elastic energy due to their bending [18].…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…However, the fraction of the surface area covered by the nanowires remains unchanged, which rules out radial growth of nanowires as the origin of coalescence. Instead, we have found that the nanowires bundle together after reaching a certain critical height to reduce the surface energy of their side facets at the expense of the elastic energy due to their bending [18].…”
Section: Introductionmentioning
confidence: 84%
“…For an estimate, consider two hexagonal nanowires with side facet width a = 10 nm at a distance l = 30 nm between their side facets. The distance between the nanowire centers is then l + 2a = 50 nm, which corresponds to the mean distance between nanowires for a density of 4×10 10 cm −2 , the typical density of nucleated nanowires before the bundling starts [18]. The critical height given by Eq.…”
Section: A Elastic Relaxationmentioning
confidence: 99%
See 3 more Smart Citations